Role of Forests in Mitigating Air Pollution - Pokhriyal, T. C.; Subba Rao, B. K. (Indian Forester, 1986)
The role of forest in soil and water conservation is well recognised. This paper examines the role of forests from a new point of view viz. in mitigating air pollution. A list oC pollution tolerant free specics has also been given.